1984
DOI: 10.1128/aac.26.4.535
|View full text |Cite
|
Sign up to set email alerts
|

Synergism at clinically attainable concentrations of aminoglycoside and beta-lactam antibiotics

Abstract: We evaluated the in vitro synergistic activity at clinically attainable concentrations of combinations of aminoglycoside and ,-lactam antibiotics against 30 gentamicin-resistant clinical isolates of gram-negative bacilli. All 56 pairs of 4 aminoglycosides and 14 1-lactams were evaluated. Combinations with amikacin demonstrated inhibitory synergistic activity in 29% of the assays, as compared with 22% for netilmicin (P = 0.018), 17% for gentamicin (P < 0.001), and 13% for tobramycin (P < 0.001 Antimicrobial syn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
10
1
1

Year Published

1986
1986
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(14 citation statements)
references
References 23 publications
2
10
1
1
Order By: Relevance
“…In contrast to studies reported previously (9,12), we have shown a significant incidence of synergy (45%) when imipenem and amikacin were combined and tested against imipenem-susceptible isolates of P. aeruginosa. These findings would support previous observations of increased rate of killing of P. aeruginosa by the combination of imipenem and amikacin (19).…”
contrasting
confidence: 54%
“…In contrast to studies reported previously (9,12), we have shown a significant incidence of synergy (45%) when imipenem and amikacin were combined and tested against imipenem-susceptible isolates of P. aeruginosa. These findings would support previous observations of increased rate of killing of P. aeruginosa by the combination of imipenem and amikacin (19).…”
contrasting
confidence: 54%
“…To our knowledge, experience with P. aeruginosa endocarditis is lacking. On the other hand, in comparison with the other aminoglycosides, amikacin has been found in some studies to be less nephrotoxic (10,20), more often resulting in synergism when it is combined in vitro with the newer antipseudomonal ,B-lactams against P. aeruginosa, including multiresistant strains (13,16,17). (16-39; 10) a After 5 h, none of the antibiotics was detected in serum (n = 8 tests).…”
Section: Methodsmentioning
confidence: 99%
“…The definition of synergy was established with the follow- (15). For the purpose of this study, antibiotic concentrations approximating clinically achievable ranges were mezlocillin, '64 ,ug/ml; piperacillin, .64 jig/ml; ticarcillin, c64 ,ug/ml; amikacin s16 jig/ml; gentamicin, c4 ,ug/ml; netilmicin, .8 ,ug/ml; and tobramycin, c4 ,ug/ml (21).…”
Section: Methodsmentioning
confidence: 99%
“…Moreover, these antimicrobial agents have been found to be especially useful when combined with an aminoglycoside (AMG) in the treatmnent of severe infections with gram-negative bacilli (1,2), perhaps reflecting their in vitro synergistic activity (10,11,13,15,16,19,24).…”
mentioning
confidence: 99%